Low‐voltage commercial super‐capacitor response to periodic linear‐with‐time current excitation: a case study. Issue 3 (19th April 2017) - Elwakil, Ahmed S.; Radwan, Ahmed G.; Freeborn, Todd J.; Allagui, Anis; Maundy, Brent J.; Fouda, Mohamed
Abstract : The response of a commercial super‐capacitor to an applied periodic current excitation in the form of a triangular waveform is investigated in this study. This waveform has a linear‐with‐time variation which enables linear charging and discharging of the device. A model consisting of a linear resistance R s and a constant phase element is used to describe the super‐capacitor impedance and expressions for the voltage across the device, the power, and stored energy are derived using concepts from fractional calculus. Experimental results are shown and an application of the study to super‐capacitor parameter extraction is described.